Integrated model framework for the evaluation and prediction of the water environmental carrying capacity in the Guangdong-Hong Kong-Macao Greater Bay Area - Xiaoyan Wang (Elsevier, 2021)
Rapid economic development and continuous population expansion have placed increasing pressure on the regional water environment. Maintaining a good water environment is the foundation for the sustainable development of human society. Therefore, an overall understanding of the regional water environment carrying capacity (WECC) is of great significance to promote regional sustainable development. In this study, a novel integrated model framework is proposed to comprehensively evaluate and predict the WECCs of 9 cities in the Guangdong-Hong Kong-Macao Greater Bay Area by coupling the entropy weight method, multi-objective linear weighting function, cloud model and Markov chain. Furthermore, an obstacle degree model is used to explore the major factors affecting the WECC in the study area. The results indicate that the WECCs of 9 cities from 2013 to 2018 show an overall improving trend, and the highest average WECC appears in Shenzhen (0.59) with a good state, while those of the other eight cities are in a medium state. From 2021 to 2030, it is predicted that the WECCs of the 9 cities will present gradual and specific changes, with the WECC of Shenzhen developing from a good to an excellent state, the WECCs of Guangzhou, Zhuhai, Huizhou, Dongguan and Jiangmen developing from medium to good, and the WECCs of Foshan, Zhongshan and Zhaoqing maintaining medium states for a long time. The main factors obstructing the WECC in the Greater Bay Area are water resources per capita, ecological water use rate, wastewater discharge per million yuan GDP and proportion of the tertiary industry, which should give priority in future development. This framework may contribute significantly to providing an effective scientific reference for regional water environmental planning and management.